Vivência do processo reprodutivo por homens pais: um olhar através dos estereótipos de gênero - Gusmão, Cleonides Silva Dias (2019)
This study aimed to investigate the gender stereotypes that male parents have and how they experience the reproductive process, addressing contraception, abortion, pregnancy, prenatal care, childbirth and paternity. In order to comply with this objective, two empirical studies of qualitative character were performed, with non-probabilistic sampling and for convenience. The first study aimed to investigate the gender stereotypes that parents have. In this study, 20 male parents participated (mean age = 32.60 years, SD = 6.08). It was used a semi-structured interview composed by the evocation, enunciation, and inquiry to investigate the gender stereotypes. Data analysis was performed through the Categorical Analysis, which allowed the extraction of two categories and seventeen subcategories. The two categories refer to Female and Male and the subcategories denounced the participation of the participants in the division of traditional roles between men and women, highlighting the female stereotypes of Sensitivity, Care, Delicacy and Fragility; and the male stereotypes of Provision of Resources, Insensitivity, Violence, and Strength. The second study had the objective of investigating the male experiences of the reproductive process. The same men who composed the sample of the first study participated in this study. We used an in-depth interview about the reproductive process for data collection. Data analysis was performed through the Categorical Analysis, which allowed the identification of five subcategories for the Contraception category, four subcategories for the Pregnancy category, three subcategories for the Abortion category, five subcategories for the Prenatal category, five subcategories for the Childbirth category, and four subcategories for category Paternity. Inequalities in relation to the reproductive process were unraveled by the participants, revealing a departure from the man of this process, based on gender stereotypes. Although at times the participants' opinions were focused on equality between partners, the descriptions of their actions denounced the inequality experienced. In general, these studies allowed the conclusion that gender stereotypes influence the way men interpret and behave in the reproductive process, serving as a means to justify the inequalities reported in the experience of this process. In this sense, these studies point to the importance of the restructuring of gender stereotypes with the aim of promoting gender equality, specifically regarding the experience of the reproductive process.